Circular RNA circKIF4A Sponges miR-375/1231 to Promote Bladder Cancer Progression by Upregulating NOTCH2 Expression - Shi, Ying-rui; Wu, Zheng; Xiong, Kun; Liao, Qian-jin; Ye, Xu; Yang, Pei; Zu, Xiong-bing (Frontiers in Pharmacology, 2020)
Circular RNAs (circRNAs) have been found to be important mediators of many biological processes in the growth and metastasis of various cancers. However, the potential roles of most circRNAs in the progression of bladder cancer remain unclear. In this research, we investigate the role of circKIF4A (hsa_circ_0007255) in the development and progression of bladder cancer. Detected by qRT-PCR analysis, circKIF4A was significantly upregulated in bladder cancer tissues and cell lines. We conducted CCK-8, colony-formation, transwell and mouse xenograft assays to explore the function of circKIF4A in bladder cancer. Functionally, knockdown of circKIF4A inhibited the proliferation and colony-formation ability of bladder cancer cells. Migration and metastatic ability were dramatically decreased after transfection with small interfering RNA targeting circKIF4A in both in vitro and in vivo assays. Mechanically, luciferase reporter assays and RNA immunoprecipitation assays were carried out to elucidate the underlying molecular mechanism of circKIF4A. The results revealed that circKIF4A sponges miR-375/1231 to promote bladder cancer progression by upregulating NOTCH2. Generally, our research unveils the essential role of circKIF4A-miR-375/1231-NOTCH2 axis in bladder cancer progression possibly via the competing endogenous RNA mechanism.